HIV Infection Is Associated With Downregulation of BTLA Expression on Mycobacterium tuberculosis-Specific CD4 T Cells in Active Tuberculosis Disease - Barham, Morgan S.; Abrahams, Deborah A.; Khayumbi, Jeremiah; Ongalo, Joshua; Tonui, Joan; Campbell, Angela; de Kock, Marwou; Ouma, Samuel Gurrion; Odhiambo, Felix Hayara; Hanekom, Willem A.; Gandhi, Neel R.; Day, Cheryl L. (Frontiers in Immunology, 2019)
Nearly a quarter of the global population is infected with Mycobacterium tuberculosis (Mtb), with 10 million people developing active tuberculosis (TB) annually. Co-infection with HIV has long been recognized as a significant risk factor for progression to TB disease, yet the mechanisms whereby HIV impairs T cell-mediated control of Mtb infection remain poorly defined. We hypothesized that HIV infection may promote upregulation of inhibitory receptors on Mtb-specific CD4 T cells, a mechanism that has been associated with antigen-specific T cell dysfunction in chronic infections. Using cohorts of HIV-infected and HIV-uninfected individuals with latent Mtb infection (LTBI) and with active TB disease, we stimulated peripheral blood mononuclear cells (PBMC) for 6 hours with Mtb peptide pools and evaluated co-expression profiles of the inhibitory receptors BTLA, CTLA-4, and PD-1 on IFN-g+/TNF-a+ Mtb-specific CD4 T cells. Mtb-specific CD4 T cells in all participant groups expressed predominately either one or no inhibitory receptors, unlike cytomegalovirus- and HIV-specific CD4 T cells circulating in the same individuals, which were predominately CTLA-4+PD-1+. There were no significant differences in inhibitory receptor expression profiles of Mtb-specific CD4 T cells between HIV-uninfected and HIV-infected individuals with LTBI. Surprisingly, BTLA expression, both alone and in combination with CTLA-4 and PD-1, was markedly downregulated on Mtb-specific CD4 T cells in HIV-infected individuals with active TB. Together, these data provide novel evidence that the majority of Mtb-specific CD4 T cells do not co-express multiple inhibitory receptors, regardless of HIV infection status; moreover, they highlight a previously unrecognized role of BTLA expression on Mtb-specific CD4 T cells that could be further explored as a potential biomarker of Mtb infection status, particularly in people living with HIV, the population at greatest risk for development of active TB disease.